Dihydropyridine calcium blockers do not interfere with non-rapid eye movement sleep - Han, GoEun; Matsumoto, Sumire; Diaz, Javier; Greene, Robert W.; Vogt, Kaspar E. (Frontiers in Neuroscience, 2022)
Non-rapid eye movement (NREM) sleep is tightly homeostatically regulated and essential for survival. In the electroencephalogram (EEG), oscillations in the delta (0.5–4 Hz) range are prominent during NREM sleep. These delta oscillations are, to date, the best indicator for homeostatic sleep regulation; they are increased after prolonged waking and fade during NREM sleep. The precise mechanisms underlying sleep homeostasis and the generation of EEG delta oscillations are still being investigated. Activity-dependent neuronal calcium influx has been hypothesized to play an important role in generating delta oscillations and might be involved in downstream signaling that mediates sleep function. Dihydropyridine blockers of L-type voltage-gated calcium channels (VGCCs) are in wide clinical use to treat hypertension and other cardiovascular disorders and are readily blood-brain-barrier penetrant. We therefore, wanted to investigate their potential effects on EEG delta oscillation and homeostatic NREM sleep regulation in freely behaving mice. In vivo two-photon imaging of cortical neurons showed larger spontaneous calcium transients in NREM sleep compared to waking. Application of the dihydropyridine calcium blocker nicardipine significantly reduced cortical calcium transients without affecting the generation of delta oscillations. Nicardipine also did not affect EEG delta oscillations over 24 h following application. The time spent in NREM sleep and NREM episode duration was also not affected. Thus, acute block of calcium entry through L-type VGCCs does not interfere with EEG delta oscillations or their homeostatic regulation, despite prior evidence from calcium channel knockout mice.